Trap-assisted monolayer ReSe2/Si heterojunction with high photoconductive gain and self-driven broadband photodetector. - Jo, Beomsu; Seo, Kanghoon; Park, Kyumin; Jeong, Chaewon; Poornaprakash, Bathalavaram; Lee, Moonsang; Ramu, Singiri; Hahm, Myung Gwan; Kim, Young Lae (Frontiers in Materials, 2024)
The development of photodetectors is crucial in fields such as optical communication, image sensing, medical devices and military equipment, where high sensitivity is paramount. We fabricated an ambipolar photodiode using monolayer triclinic ReSe2, synthesized by chemical vapor deposition on p-type Si substrate. The photodetector has a broadband response range from 405 to 1100 nm. The device exhibits high sensitivity to NIR radiation with a high Iph/Idark (ON/OFF) ratio of 5.8 × 104, responsivity (R) of 465 A/W, and specific detectivity (D) of 4.8 × 1013 Jones at open circuit voltage (Voc), indicating photovoltaic behavior. Our ReSe2/Si heterojunction photodetector also exhibits low dark current of 1.4 × 10-9 A and high external quantum efficiency (EQE) of 54368.2% for 1060 nm at -3 V, demonstrating a photoconductive gain. The maximum responsivity (R = 465 A/W) can be achieved at -3 V reverse bias under 1060 nm. The device has a high ideality factor (4.8) and power coefficient (α = 0.5), indicating the presence of interface and sub-gap states that enhance device responsivity at lower illumination intensities by re-exciting trapped carriers into the conduction band. Our results offer important insights into the underlying photo-physics of the ReSe2/Si heterojunction and propose promising avenues for developing advanced broadband photodetectors of high performance.